Dilogarithm Identities for Sine-Gordon and Reduced Sine-Gordon Y-Systems - Tomoki Nakanishi; Roberto Tateo (Symmetry, Integrability and Geometry: Methods and Applications, 2010)
We study the family of Y-systems and T-systems associated with the sine-Gordon models and the reduced sine-Gordon models for the parameter of continued fractions with two terms. We formulate these systems by cluster algebras, which turn out to be of finite type, and prove their periodicities and the associated dilogarithm identities which have been conjectured earlier. In particular, this provides new examples of periodicities of seeds.